2011
DOI: 10.33899/earth.2011.5551
|View full text |Cite
|
Sign up to set email alerts
|

Nannobiostratigrphy of Shiranish Formation in Balad Well No. 8, Northern Baghdad, Iraq

Abstract: Eight samples of Shiranish Formation were obtained from Balad well No. 8, (northern Baghdad) central Iraq. Details investigated carried out identify calcareous nannofossils, where identified sixteen species; eleven descried from other region and five left under open name because of lack of material or rare of samples, On the basis of stratigraphic distribution of the species, two biozones proposed these are : 2-Reinhardites levis Interval Biozone(CC24) 1-Tranolithus phacelosus Interval Biozone(CC23b)The propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…7 and 8), These biozones are : 1 -Tranolithus phacelosus [35] Interval Biozone (CC 23) Identification: It is Interval biozone for Tranolithus phacelosus [35], recorded by the Last Appearance Datum (LAD) of the species Eiffilithus eximus Reinhardt (1965), and extends to the Last Appearance Datum (LAD) of the species Tranolithus phacelosus [35], and the thickness of this biozone is about (18 meters), within the lower part of the Shiranish Formation Correlation: This zone is compared with CC23 (Tranolithus phacelosus) zone which studied by the [33] that aged of the late Campanian to early Maastrichtian, and compared with UC16, UC17 zone that is studied by [40], that aged Campanian to early Maastrichtian age. On local scale its compared with Tranolithus phacelosus zone that is recorded by the [22,65,66,67], that is also extends un age from Campanian to early Maastrichtian. Its also recorded as index of zone CC23 from the lower part of the Tanjero Formation, Sulaimani area by [68].…”
Section: Discussionmentioning
confidence: 99%
“…7 and 8), These biozones are : 1 -Tranolithus phacelosus [35] Interval Biozone (CC 23) Identification: It is Interval biozone for Tranolithus phacelosus [35], recorded by the Last Appearance Datum (LAD) of the species Eiffilithus eximus Reinhardt (1965), and extends to the Last Appearance Datum (LAD) of the species Tranolithus phacelosus [35], and the thickness of this biozone is about (18 meters), within the lower part of the Shiranish Formation Correlation: This zone is compared with CC23 (Tranolithus phacelosus) zone which studied by the [33] that aged of the late Campanian to early Maastrichtian, and compared with UC16, UC17 zone that is studied by [40], that aged Campanian to early Maastrichtian age. On local scale its compared with Tranolithus phacelosus zone that is recorded by the [22,65,66,67], that is also extends un age from Campanian to early Maastrichtian. Its also recorded as index of zone CC23 from the lower part of the Tanjero Formation, Sulaimani area by [68].…”
Section: Discussionmentioning
confidence: 99%
“…Quaternary deposits extended widely in the study area by the processes of weathering and erosion which occurred in the region by water current and wind movement, these sediments consisting of mixture of gravel, sand, silt, and clay, The rates of these components varying between one region and another [14], usually these sediments friable, which leads to find a good layer for water penetration into groundwater reservoirs. It include deposits of Pleistocene Holocene [15], and there are several types of Quaternary deposits such as River Terraces, Flood plain, Polygenetic deposits, Aeolian Deposits, Sabkha, [16]. Tharthar valley is the deepest and longest one in the region, and beyond the limits of the study area is extending from Mount Sinjar, north to TharThar Lake south [17], several notably valleys flows to Tharthar such as Althrether, Al-Amer and Qaiberah, Ibdan and Ibrah [5], as shown in (Figure 2).…”
Section: Geology Of the Study Areamentioning
confidence: 99%
“…P), [19], the speed became zero on the bottom of the section (the valley bottom), so, the average velocity must be calculated and adopted in the calculations of discharge, the experimental studies suggested that the average flow velocity is on 0.6 of the total depth at the deepest point in a flow section [20]; [21], figure (6). The method that described in [20]; [19], modified to calculate the average velocity, 10 levels were selected to calculate the average velocity, the flow sections of these levels plotted, the value of the surface velocity used as velocity of upper contour line, and the zero value for the contour that in contact with the bottom of the valley (wetted perimeter), and then insert intracontour lines (between the lowest and highest contours), the values of flow velocity distributed between the contour lines, as in figures (7,8,9,10,11,12,13,14,15,16). Then the partial areas between each two successive contour lines were measured, and the percentages of these areas to the total area of flow section were calculated using ARC GIS and thus the average velocity calculated according to the following equation:…”
mentioning
confidence: 99%
“…The thickness of this biozone is 40 meter from the section. This biozone is correlated with CC22 (Quadrum trifidum biozone), which is studied by [10 ] and aged as the middle to late Campanian, and correlated upper part of UC15 biozone that is studied by [11 ] which aged middle to late Campanian age, and correlated with CC22 is studied by [13 ] aged late Campanian age, and correlated with CC22 is studied by [14] aged late Campanian age, and correlated with CC22 is studied by [15] aged late Campanian age, and correlated with CC22 which is studied by [4] and aged as the late Campanian age, Therefore we suggest the late Campanian [12] (Figs. 7,8).…”
Section:  Quadrum Trifidum Interval Biozonementioning
confidence: 99%